The Newfoundland Provincial Government: Culture, Nationalism, and Identity, 1949-1989 - Conway, Shannon (Newfoundland and Labrador Studies)

(untitled) (Faculty of Arts, Memorial University, 2022)
Newfoundland’s post-Confederation cultural revival is a significant factor in how Newfoundlanders were able to maintain their distinct identity within Canada. Another considerably related factor is the role the provincial government played in the decades following Confederation. As F.L. Jackson wrote in 1984, “the conservation of Newfoundland’s cultural heritage is [...] only really possible if there is also a conservation of Newfoundland’s political integrity and autonomy.” During this period, there was an increase in cultural and heritage initiatives, particularly from the Progressive Conservative provincial governments from the mid-1970s onward. This government involvement reflects the earlier developments in the arts scene and within the academic community at Memorial University that came to be known as the cultural revival. The provincial government’s utilization of the cultural revival movement to leverage political support from their citizenry during inter-governmental negotiations with the federal government demonstrates an evolution in the province from a purely cultural nationalism, to a more developed economic and political nationalism by the 1980s.